2006
DOI: 10.3989/scimar.2006.70s1161
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-plankton characteristics and their relationship with sardine and anchovy distributions on the French shelf of the Bay of Biscay

Abstract: SUMMARY:The spatial pattern in hydro-plankton and fish distributions and their relationship were analysed based on the spring 2000 fisheries acoustic survey. The importance of this survey was that it was a multi-disciplinary platform which collected an extensive set of parameters in the hydro-plankton leading to a potentially finer description of hydro-plankton conditions and fish habitats. More than 50 variables were measured on a grid of stations, in four compartments of the ecosystem: hydrology, nutrients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…However, they contrast with what was observed for the eastern Mediterranean and the Bay of Biscay. In the former case, sardines were associated with warmer waters (Giannoulaki et al 2011), while in the latter no preferences were observed in relation to hydrographic conditions (Petitgas et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, they contrast with what was observed for the eastern Mediterranean and the Bay of Biscay. In the former case, sardines were associated with warmer waters (Giannoulaki et al 2011), while in the latter no preferences were observed in relation to hydrographic conditions (Petitgas et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Sardine is a small eurythermic and euryhaline clupeoid, distributed in the northeastern Atlantic Ocean from the southern Celtic Sea and the North Sea to Senegal, and across the western and northern Mediterranean Sea (Parrish et al 1989). It generally inhabits waters with temperatures ranging from 8 to 24°C and salinities ranging from 30 to 38 psu (Petitgas et al 2006). Sardine populations support important fisheries across their distribution area (Whitehead 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These have combined acoustic with oceanographic data (e.g. Paramo & Roa 2003, Petitgas et al 2006, Peltonen et al 2007, Lebourges-Dhaussy et al 2009, Zwolinski et al 2010 or with satellite-based environmental data (Bellido et al 2008, Giannoulaki et al 2008, Tugores et al 2010, Zwolinski et al 2011. Habitat characteristics and fish densities have been mapped at comparable extents and resolutions in coral reef and other coastal ecosystems by integrating the output of several sonar systems on multibeam hydrographic survey vessels (Kracker et al 2011).…”
Section: Predator-prey Relationships and Habitat Requirementsmentioning
confidence: 99%
“…The day-time geographic distribution of anchovy in the Bay of Biscay in May was found to be associated with turbid, nutrient-rich coastal waters in the Southern part, while the distribution of sardine during the same period was unrelated to water mass characteristics (Petitgas et al 2006). As a consequence, the day-time geographic distribution of sardines is more variable between years but also more widespread (Massé 1996;Massé and Gerlotto 2003).…”
Section: Geographic Distributionsmentioning
confidence: 99%
“…factors structured at the regional scale. The spatial distribution of anchovy at the mesoscale (dozen of km) displayed significant correlation with plankton communities commonly found in river plumes and in the southern coastal areas of the Bay of Biscay (Petitgas et al 2006). Moreover, small pelagic species generally undergo regional scale migrations, thought to be evolutionary adaptations to seasonal changes in food availability or search for spawning habitats favourable for offspring survival (Fréon et al 2005).…”
Section: Spatial Distribution Of Small Pelagic Fish In the Bay Of Biscaymentioning
confidence: 99%